2017
DOI: 10.1002/2016jd025978
|View full text |Cite
|
Sign up to set email alerts
|

Temperature changes in Three Gorges Reservoir Area and linkage with Three Gorges Project

Abstract: The Three Gorges Project (TGP) is one of the largest hydroelectric projects throughout the world. It has brought many benefits to the society but also led to endless debates about its environmental and climatic impacts. Monitoring the spatiotemporal variations of temperature in the Three Gorges Reservoir Area (TGRA) is important for understanding the climatic impacts of the TGP. In this study, we used remote sensing‐based land surface temperature (LST) and ground‐measured air temperature data to investigate te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 77 publications
(109 reference statements)
0
23
0
Order By: Relevance
“…In general, the impact decreased with increasing distance away from the TGR (Degu et al, ). Previous studies found the construction of the TGD can decrease daily mean and maximum temperatures along the narrow waterway of the TGR (Li and Tang 2014; Miller et al, ; Zhang et al, ; Chen et al, ; Song et al, ). Chen et al () suggested that the changes in surface air temperature is −0.1 °C within the 20‐km buffer along the reservoir.…”
Section: Model Validationmentioning
confidence: 95%
See 2 more Smart Citations
“…In general, the impact decreased with increasing distance away from the TGR (Degu et al, ). Previous studies found the construction of the TGD can decrease daily mean and maximum temperatures along the narrow waterway of the TGR (Li and Tang 2014; Miller et al, ; Zhang et al, ; Chen et al, ; Song et al, ). Chen et al () suggested that the changes in surface air temperature is −0.1 °C within the 20‐km buffer along the reservoir.…”
Section: Model Validationmentioning
confidence: 95%
“…Some studies suggested that the construction of the TGD can slightly alter the local (~10 km) meteorological conditions such as temperature and moisture along the narrow waterway of the TGR (Chen et al, 2009;Li et al, 2017;Miller et al, 2005;Song et al, 2017;Wu et al, 2012;Zhang et al, 2004;Zhang et al, 2005). It is argued that the increased area of water surface enhances local evaporation, thus reducing local temperature and increasing local atmospheric moisture (Gwynne & Li, 1992;Miller et al, 2005;Niyogi et al, 2010).…”
Section: Intrductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the vegetation dynamics associated with the TGR, it was important to separate the effect of the TGR from the large-scale climate impacts. We adopt the method as used in Song's research [14]. In our study, the regional background was defined as the 100 km spatial buffer from the TGRA.…”
Section: Vegetation Dynamics Considering Climate Impactsmentioning
confidence: 99%
“…In this study, we aim to investigate empirical evidence of contrasting water level-climate -vegetation feedback across the TGD area by using causal inference methods. The Three Gorges Reservoir (TGR) covers the reach of the Yangtze River between Chongqing and Yichang with a total water surface area of 1080 km 2 at the water level of 175 m [14]. After two tentative impounding operations to the elevations of 135 m and 156 m above the sea level at 10 June 2003, and 27 October 2006, respectively, the TGR started impounding water after the flood season with the water level of 175 m above mean sea level reached 26 October 2010.…”
Section: Introductionmentioning
confidence: 99%